Influence of concomitant antiretroviral therapy on the rate of sustained virological response to pegylated interferon plus ribavirin in hepatitis C virus/HIV-coinfected patients - Pineda, Juan A.; Mira, José A.; Gil, Ignacio de los Santos; Valera-Bestard, Bárbara; Rivero, Antonio; Merino, Dolores; Girón-González, José A.; Ríos-Villegas, María J.; González-Serrano, Mercedes; Collado, Antonio; García-García, José A.; Carrillo-Gómez, Raquel; et al. (Journal of antimicrobial chemotherapy, 2007)
Objectives To investigate whether concomitant antiretroviral therapy (ART) is a predictor of sustained virological response (SVR) in human immunodeficiency virus (HIV)/hepatitis C virus (HCV)-coinfected patients treated with pegylated interferon plus ribavirin. Methods Three hundred and ten HIV/HCV-coinfected patients on pegylated interferon plus ribavirin treatment, 258 of them with concurrent ART, were included in this retrospective multicentre study. The predictors of SVR were evaluated. Results SVR was shown by 114 (37%) subjects. HCV genotype 2 or 3, plasma HCV-RNA load lower than 600 000 IU/mL, an exposure to the therapy against HCV infection ≥80% of the planned dose and baseline CD4 cell counts higher than or equal to 300/mm3 were predictors of SVR. Likewise, patients without ART and those receiving a combination including tenofovir or stavudine plus lamivudine plus a protease inhibitor (PI) or a non-nucleoside reverse transcriptase inhibitor (NNRTI) showed a higher SVR rate than the subjects who were on other ART strategies at baseline [44%, 44% and 29%, respectively; adjusted odd ratio (95% CI) for no ART = 1.96 (1.07–4.76), P = 0.025, and for ART including tenofovir or stavudine plus lamivudine plus a PI or a NNRTI = 2.08 (1.16–3.70), P = 0.014]. Conclusions The ART strategy on starting therapy with pegylated interferon plus ribavirin is a predictor of SVR in HIV/HCV-coinfected patients. Subjects without ART and those receiving combinations of a PI or a NNRTI with a nucleos(t)ide backbone of tenofovir or stavudine plus lamivudine respond better than those who receive other regimens.